Catenated and spirocyclic polychalcogenides from potassium carbonate and elemental chalcogens. Issue 99 (27th November 2019) - Liebing, Phil; Kühling, Marcel; Swanson, Claudia; Feneberg, Martin; Hilfert, Liane; Goldhahn, Rüdiger; Chivers, Tristram; Edelmann, Frank T.
Abstract : Reaction of potassium carbonate with elemental sulfur or selenium in acetone in the presence of [PPN]Cl (PPN = (Ph3 P)2 N) produces catena -[S12 ] 2−, the longest structurally characterised polysulfide dianion, or spiro -[Se11 ] 2− as ion-separated [PPN] + salts. Abstract : The reaction of potassium carbonate with elemental sulfur or selenium in acetone in the presence of [PPN]Cl (PPN = (Ph3 P)2 N) produces catena -[S12 ] 2−, the longest structurally characterised polysulfide dianion, or spiro -[Se11 ] 2− as ion-separated [PPN] + salts.